Caveolae-Mediated Transcytosis and Its Role in Neurological Disorders - Kunjian Yang; Qian Li; Yushuang Ruan; Yuanpeng Xia; Zhi Fang (Biomolecules)
The blood–brain barrier (BBB) controls the flow of substances to maintain a homeostatic environment in the brain, which is highly regulated and crucial for the normal function of the central nervous system (CNS). Brain endothelial cells (bECs), which are directly exposed to blood, play the most important role in maintaining the integrity of the BBB. Unlike endothelial cells in other tissues, bECs have two unique features: specialized endothelial tight junctions and actively suppressed transcellular vesicle trafficking (transcytosis). These features help to maintain the relatively low permeability of the CNS barrier. In addition to the predominant role of tight junctions in the BBB, caveolae-mediated adsorptive transcytosis has attracted much interest in recent years. The active suppression of transcytosis is dynamically regulated during development and in response to diseases. Altered caveolae-mediated transcytosis of bECs has been reported in several neurological diseases, but the understanding of this process in bECs is limited. Here, we review the process of caveolae-mediated transcytosis based on previous studies and discuss its function in the breakdown of the BBB in neurological disorders.